Brazil and United States: An analysis of foreign and bilateral tradein 2005-2016 - Samuel Santos de Oliveira; Camila do Carmo Hermida (Universidade Estadual de Alagoas, 2021)
Trade relations between Brazil and the United States are old and date back to Brazil's independence. The United States has always been an important trade partner, however, its weight in the Brazilian trade baskethas been reduced in parallel with the intensification of international fragmentation of production and the growing emphasis of Brazil's partnership with China. The aim of the article is to present a comparative analysis of the insertion of Brazil and the United States in international trade and thetrade relationship between them in the recent period (2005-2016). Statistical analysis using COMTRADE data provides that the main Brazilian export products to the United States have a higher degree of technological sophistication than the standard for theworld. The results also point to a greater concentration on exports than on imports from Brazil and a trend towards growth in the degree of their concentration. Brazil has a much greater specialization in products with low technological intensity, but a greater presence of products with more technological intensity in exports to the United States, which reveals the importance of their relationshipin the recent period.